Exploring effector protein dynamics and natural fungicidal potential in rice blast pathogen Magnaporthe oryzae - Jannatul Ferdousy; Tanjin Barketullah Robin; Mst Sanjida Nasrin; Istiak Ahmed; Tawsif Hossain; Md Mehedi Hasan; Mehrab Hassan Soaeb; Md. Ahsanul Tamim; Nusrat Jahan Yeasmin; Ummay Habiba; Nadim Ahmed; Nurul Amin Rani; et al. (PLoS ONE, 2025)
Rice blast, caused by Magnaporthe oryzae, is one of the most destructive fungal diseases in rice, resulting in major economic losses worldwide. Genetic and genomic studies have identified key genes and proteins, such as AvrPik variants and MAX proteins, that are crucial for the pathogen’s virulence. These effector proteins interact with specific alleles of the Pik gene family on rice chromosome 11, modulating the host’s immune response. In this study, we investigated 35 plant-derived metabolites known for their antifungal properties as potential fungicides against M. oryzae. Using molecular docking, we identified Hecogenin and Cucurbitacin E as strong binders to MAX40 and APIKL2A proteins, which are essential for the fungus’s immune evasion and pathogenicity. Molecular dynamics simulations further confirmed that these compounds form stable, strong interactions with the target proteins, validating their potential as therapeutic agents. Additionally, the compounds were evaluated based on Lipinski’s rule of five and toxicity predictions, indicating their suitability for agricultural use. These results suggest that Hecogenin and Cucurbitacin E could serve as promising lead candidates in the development of novel fungicides for rice blast, offering new strategies for crop protection and sustainable agricultural practices.